Éthique et évaluation monétaire de l'environnement : la nature est-elle soluble dans l’utilité ? - Julien Milanesi (VertigO)
"The nature disappears because it has no economic value ", here is the hypothesis that underlies the recent profusion of state commissions and scientific works on the monetary evaluation of environmental goods. Put in these terms, the interrogation is not to know if the nature has an economic value or not, but to measure this one. The scientific questions linked to these methods are therefore usually defined as technical issues, when their main problem may be philosophical, related to the type of moral link that exists between humans and their environment. The analysis of the theoretical foundations of the contingent valuation method indeed shows that to value environmental goods the individuals have to be in capacity to substitute a state of the environment for their monetary income. They therefore cannot have moral links with these goods that could prevent possibilities of substitution. This hypothesis is however contested by numerous works on environmental ethics that finally raise the question of the signification of the numbers usually interpreted as monetary values of environmental goods.